Genetically modified food : a short guide for the confused - Rees, Andrew, 1961- (Pluto Press, 2006)
-- The perfect guide for anyone who wants to know more about genetically modified crops -- what they are, how many countries already use them, and why they're a problem -- 'Rees unmasks the biotech industry's horrific tactics in their race to take over ou.